Propofol Versus Methohexital in Electroconvulsive Therapy: Impact on Treatment Efficacy and Adverse Effects. A Systematic Literature Review and Meta‐Analysis - Huoponen, Saara H.; Sisa, Katrin; Saari, Tom; Taittonen, Markku; Ahlmen-Laiho, Ulla (Wiley, 2026)
Background: Electroconvulsive therapy (ECT) is a widely used treatment for depression, but the choice of the anesthetic that is used for induction may affect both clinical outcomes and the occurrence of adverse effects (AEs). Propofol and methohexital are frequently used in Finland, yet their relative impact on treatment efficacy and AEs remains uncertain.
Methods: We conducted a systematic literature review and meta-analysis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Electronic databases were searched up to January 21, 2025. Studies comparing propofol and methohexital in adult patients receiving ECT for depression and utilizing numeric scales for depression assessment were included. The primary outcome was the clinical treatment response, defined by the number of ECT sessions required to achieve remission. The secondary outcome was the variation of AEs associated with ECT between comparator groups. We included eight studies in the final analysis with 194 patients in the propofol group and 198 patients in the methohexital group. Five of the studies were randomized controlled trials and three were retrospective cohort studies. Three randomized controlled trials with 131 patients: 62 (47%) in propofol group and 69 (53%) in methohexital group were included in meta-analysis.
Results: The number of ECT sessions required for recovery did not differ between groups. All studies demonstrated effective alleviation of depression through ECT, regardless of anesthetic choice. However, AEs were inconsistently reported, and a comprehensive overview of the topic was not possible.
Conclusions: Low-quality evidence suggests equal efficacy of propofol compared to methohexital with regard to clinical remission of depression after ECT.
Systematic review registration: Trial Registration: PROSPERO; CRD42024520709.
Editorial comment: This systematic review and meta-analysis presents the available but limited and low-quality evidence in this study area, and supports an interpretation that propofol and methohexital have similar efficacy when facilitating electroconfulsive therapy as treatment for depression, to relieve depression symptoms.